Effects of selective heart rate reduction with ivabradine on LV function and central hemodynamics in patients with chronic coronary syndrome. (June 2021) - Hohneck, Anna Lena; Fries, Peter; Stroeder, Jonas; Schneider, Günther; Schirmer, Stephan Henrik; Reil, Jan-Christian; Böhm, Michael; Laufs, Ulrich; Custodis, Florian
Abstract: Objectives: We assessed left ventricular (LV) function and central hemodynamic effects in patients with a heart rate (HR) at rest of ≥70 beats per minute (bpm) and chronic coronary syndrome (CCS) after long-term treatment with ivabradine compared to placebo by cardiac magnetic resonance (CMR) imaging. Methods and results: In a randomized, double-blinded, prospective cross-over design, 23 patients (18 male, 5 female) were treated with ivabradine (7.5 mg bid) or placebo for 6 months. CMR imaging was performed at baseline and after 6 and 12 months to determine LV functional parameters. Mean resting HR on treatment with ivabradine was 58 ± 8.2 bpm and 70.2 ± 8.3 bpm during placebo (p < 0.0001).There was no difference in systolic LV ejection fraction (ivabradine 57.4 ± 11.2% vs placebo 53.0 ± 10.9%, p = 0.18), indexed end-diastolic (EDVi) or end-systolic volumes (ESVi). Indexed stroke volume (SVi) (ml/m 2 ) remained unchanged after treatment with ivabradine. Volume time curve parameters reflecting systolic LV function (peak ejection rate and time) were unaffected by ivabradine, while both peak filling rate (PFR) and PFR/EDV were significantly increased. Mean aortic velocity (cm/s) was significantly reduced during treatment with ivabradine (ivabradine 6.7 ± 2.7 vs placebo 9.0 ± 3.4, p = 0.01). Aortic flow parameters were correlated to parameters of vascular stiffness. The strongest correlation was revealed for mean aortic velocity with aortic distensibility (AD) (r = −0.86 [−0.90 to −0.85], p < 0.0001). Conclusion: Long-term reduction of HR with ivabradine in patients with CCS improved diastolic function and reduced mean aortic flow velocity.